Defining an Ultrasound‐guided Regional Anesthesia Curriculum for Emergency Medicine. Issue 3 (11th December 2020) - Tucker, Ryan V.; Peterson, William J.; Mink, Jennifer T.; Taylor, Lindsay A.; Leech, Stephen J.; Nagdev, Arun D.; Leo, Megan; Liu, Rachel; Stolz, Lori A.; Kessler, Ross; Boulger, Creagh T.; Situ‐LaCasse, Elaine H.; et al.
Abstract: Objectives: Ultrasound‐guided regional anesthesia (UGRA) can be a powerful tool in the treatment of painful conditions commonly encountered in emergency medicine (EM) practice. UGRA can benefit patients while avoiding the risks of procedural sedation and opioid‐based systemic analgesia. Despite these advantages, many EM trainees do not receive focused education in UGRA and there is no published curriculum specifically for EM physicians. The objective of this study was to identify the components of a UGRA curriculum for EM physicians. Methods: A list of potential curriculum elements was developed through an extensive literature review. An expert panel was convened that included 13 ultrasound faculty members from 12 institutions and from a variety of practice environments and diverse geographical regions. The panel voted on curriculum elements through two rounds of a modified Delphi process. Results: The panelists voted on 178 total elements, 110 background knowledge elements, and 68 individual UGRA techniques. A high level of agreement was achieved for 65 background knowledge elements from the categories: benefits to providers and patients, indications, contraindications, risks, ultrasound skills, procedural skills, sterile technique, local anesthetics, and educational resources. Ten UGRA techniques achieved consensus: interscalene brachial plexus, supraclavicular brachial plexus, radial nerve, median nerve, ulnar nerve, serratus anterior plane, fascia iliaca, femoral nerve, popliteal sciatic nerve, and posterior tibial nerve blocks. Conclusions: The defined curriculum represents ultrasound expert opinion on a curriculum for training practicing EM physicians. This curriculum can be used to guide the development and implementation of more robust UGRA education for both residents and independent providers.